Reproductive conflicts in honeybee colonies - Pirk, Christian Walter Werner (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 2002)
In advanced eusocial hymenopteran societies workers have ovaries and can lay eggs, but are unable to mate. Workers are more related to their own offspring than to every other member of the colony. So worker reproduction contains both worker-worker and worker-queen conflict. The queen- worker conflict is discussed elsewhere, but if the queen mates with more than two males, worker policing should be selected to lower potential conflicts. However in the Cape honeybee it was predicted that worker policing is absent or less expressed than in other honeybee subspecies, because workers produce female offspring thelytokously. So laying workers and their offspring are nearly genetically identical, which results in the fact that other workers are as related to workers derived from eggs laid by the queen as laid by a worker. However, worker reproduction may be costly and therefore worker policing could be an evolutionary adaptation in the Cape honeybee to lower the costs derived from laying worker activity. Indeed, Cape honeybee colonies show efficient egg removal behaviour, suggesting that other factors like colony efficiency could favour egg removal behaviour. Since egg removal behaviour is a colony phenomenon, factors that affect colony performance could also affect egg removal behaviour. Egg removal behaviour was considerably affected by environmental changes, indicating that other tasks have a higher priority than egg removal behaviour. Thousands of queenright colonies of the neighbouring subspecies (A. m. scutellata) were taken over by laying A. m. capensis workers, showing that A. m. capensis workers are facultative social parasites. These observations strongly indicate that laying workers of A. m. capensis are able to evade worker policing and the inhibitory effects of the queen pheromones, but what potential strategies could these laying workers use to increase the survival of their eggs and evade the queen? On the one hand, egg removal behaviour is variable. One behavioural strategy of laying workers to achieve successful reproduction could be that they lay during periods with low egg removal behaviour. On the other hand, the inhibitory effect of the queen's pheromones diminishes with distance. Maybe the level of egg removal also depends, like the inhibitory effect of the queen pheromones, on the distance from the queen. Indeed, further away from the queen the effect of the queen pheromone and the level of egg removal is reduced, making successful worker reproduction possible. In both subspecies, A. m. capensis and A. m. scutellata, egg removal behaviour is reduced further away from the queen. In the case of A. m. scutellata egg removal is lacking further away from the queen. This explains why colonies of scutellata are so prone to takeovers by laying Cape honeybee workers. One question in the context of parasitic Cape honeybees is how they manage to get into the host colony. One way could be that they get into the colonies during a natural colony merger which is common in African bees. Two unrelated colonies merged and it took them only 24 hours to show effective integration. Because both colonies are unrelated, the potential reproductive conflict among workers should be more strongly expressed than in a normal colony, which is not the result of a merger. Therefore, the effect of nestmate recognition for eggs on the egg removal behaviour was investigated. The results suggest that workers recognise the origin of an egg and that the standard policing experiments overestimate the level of egg removal and only represent relative values. Moreover, the results show that colony specific components on the eggs are more important than a postulated queen egg marking pheromone. Finally, for the first time empirical evidence from a population of the parasitic laying Cape honeybee workers, invading thousands of colonies of A. m. scutellata in northern South Africa, for a short-sighted selection theory is presented.
Keywords: Honeybee -- Reproduction